(untitled) (Journal of Shaheed Suhrawardy Medical College, 2021)
Introduction: The emergence of antibiotics resistance bacteria is a persistent global problem affecting public health. The occurrence and widespread resistance to Imipenem among hospital bacterial isolates can constitute a significant threat to chemotherapy. Objectives: This cross-sectional study aimed to investigate the imipenem resistant pattern among gram-negative bacilli isolated from different samples in Dhaka medical college hospital. Methods: A total of 300 samples (wound swab, urine, endotracheal aspirate, blood, and sputum) were collected from July 2015 to June 2016. Two hundred four gram-negative bacilli were isolated and tested for resistance to imipenem by the disc diffusion method. Results: Among 204-gram negative bacilli, 39.21% imipenem resistance was detected by the Disc Diffusion method. 14.7% imipenem resistance gram-negative bacilli were from wound swab. 83.33% of Acinetobacter baumannii were Imipenem resistant. Conclusions: Imipenem resistance is widespread among gram-negative bacilli isolated from human infections. Imipenem resistance (39.21%) found in the study is quite worrisome. J Shaheed Suhrawardy Med Coll, December 2020, Vol.12(1); 3-5